A mini review of mycotoxin’s occurrence in food in South America in the last 5 years: research gaps and challenges in a climate change era - Foerster, Claudia; Müller-Sepúlveda, Andrea; Copetti, Marina Venturini; Arrúa, Andrea Alejandra; Monsalve, Liliam; Ramirez, María Laura; Torres, Adriana M. (Frontiers in Chemical Biology, 2024)
Mycotoxins are natural metabolites produced by species of filamentous fungi belonging mainly to the genera Aspergillus, Fusarium, Penicillium, and Alternaria, which can grow in various crops and foodstuffs. The South American climate is diverse, varying from tropical, temperate, and arid to cold, ideal for the growth of different types of fungi and mycotoxin production. This mini review aimed to describe the natural occurrence of mycotoxin in food in South America from 2018 to 2023, identifying research gaps and challenges in an era of climate change. We analyzed 53 studies, 21 from Brazil. Most of the mycotoxins analyzed in South America were the traditional and regulated mycotoxins, with variable occurrences depending on the region, climatic conditions, and methodology used. Emerging and modified mycotoxins have only been studied in Argentina and Brazil, where some studies have shown high occurrences. Given this, it is essential to strengthen food safety laboratories and surveillance capabilities and establish early warning systems. It is also essential to continue working to raise awareness of mycotoxins as a public health issue and to study and prevent the impact of climate change on soil microbial population, the new prevalence of fungi, and the profile of toxigenic species. An effective connection and collaboration between disciplines and sectors in different countries is needed to meet this research challenge.